An Oligonucleotide‐Distortion‐Responsive Organic Transistor for Platinum‐Drug‐Induced DNA‐Damage Detection. Issue 25 (13th May 2021) - Ye, Dekai; Wang, Juan; Shen, Hongguang; Feng, Xinping; Xiang, Lanyi; Jin, Wenlong; Zhao, Wenrui; Ding, Jiamin; He, Zihan; Zou, Ye; Meng, Qing; Cui, Wei; et al.
Abstract: Organic transistor with DNA‐damage evaluation ability can open up novel opportunities for bioelectronic devices. Even though trace amounts of drugs can cause cumulative gene damage in vivo, the extremely low occurrence proportion makes them hardly transduced into detectable electric signals. Here, an ultrasensitive DNA‐damage sensor based on an oligonucleotide‐distortion‐responsive organic transistor (DROT) is reported by creating controllable conformation change of double‐stranded DNA on the surface of organic semiconductors. In combination with interfacial charge redistribution and efficient signal amplification, the DROT provides an ultrasensitive single‐site DNA‐damage response with 20.5 s even upon 1 × 10 −12 m cisplatin. The high generalizability of this DROT to three generations of classical platinum drugs and gene‐relevant DNA damage is demonstrated. A biochip is further designed for intelligent damage analysis in complex environments, which holds the potential for high‐throughput biotoxicity evaluation and drug screening in the future. Abstract : With specific responsiveness to oligonucleotide distortion on the surface of organic semiconductors, a double‐stranded‐DNA‐functionalized organic thin‐film transistor can detect platinum‐drug‐induced DNA damage at single‐site level. The organic‐transistor‐based ultrasensitive DNA‐damage sensor can be further integrated into arrayed biochips for high‐throughput DNA‐damage analysis under different environmental conditions.